Analisis Waste Pada Proses Produksi Chain Wheel Gear Menggunakan Pendekatan Lean Manufacturing Pada PT Sinar Agung Selalu Sukses - pitapus rini; Maulana Fajrian; Ratna Agil Apriani (Universitas Muhammadiyah Metro, 2026)
The global automotive industry faces increasing pressure to improve productivity, quality, and cost efficiency to remain competitive. Manufacturing companies are therefore required to minimize waste and optimize production processes. This study analyzes waste reduction in the Original Equipment Manufacturer (OEM) production line at PT Sinar Agung Selalu Sukses, focusing on Chain Wheel Gear (CWG). Between January and July 2025, the production line recorded 9,903 defective units, indicating significant inefficiencies. Lean Manufacturing tools—Value Stream Mapping (VSM), the Borda method, and Fishbone Diagrams—were applied to identify dominant waste and root causes. The analysis revealed a Process Cycle Efficiency (PCE) of 35.9%, below the 50% benchmark, with defect waste identified as the most critical issue. The main contributing factors include material inconsistency, unstable process methods, operator performance, and machine conditions. A 5W+1H-based improvement plan is proposed, including operator mentoring, process standardization, preventive maintenance, and stricter material control. These improvements are expected to reduce defects, shorten lead time, and enhance production efficiency, strengthening competitiveness in Indonesia’s automotive component industry.